2014
DOI: 10.1103/physrevb.90.195205
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of intermediate-spin ferrous iron in the Earth's lower mantle

Abstract: IS state has an electronic configuration that significantly reduces the electron overlap and the iron nuclear quadrupole splitting (QS). These most probable IS states, however, are still energetically disfavored, and their QSs are inconsistent with Mössbauer spectra. We therefore conclude that IS Fe 2+ is highly unlikely in the Earth's lower mantle.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 80 publications
4
65
0
Order By: Relevance
“…Theoretical investigations indicate that the B ‐site Fe 3+ undergoes a transition from the high spin (HS) to the low spin (LS) state, while A site iron remains in the HS state, regardless of its valence [ Hsu and Wentzcovitch , ; Hsu et al ., , , ; Mohn and Trønnes , ; Yu et al ., ]. This theory‐based view has found experimental support [ Catalli et al ., , ; Lin et al ., ] but is not yet widely accepted [ Kupenko et al, ; McCammon et al ., ].…”
Section: Main Textmentioning
confidence: 99%
“…Theoretical investigations indicate that the B ‐site Fe 3+ undergoes a transition from the high spin (HS) to the low spin (LS) state, while A site iron remains in the HS state, regardless of its valence [ Hsu and Wentzcovitch , ; Hsu et al ., , , ; Mohn and Trønnes , ; Yu et al ., ]. This theory‐based view has found experimental support [ Catalli et al ., , ; Lin et al ., ] but is not yet widely accepted [ Kupenko et al, ; McCammon et al ., ].…”
Section: Main Textmentioning
confidence: 99%
“…High-pressure studies have observed the occurrence of the extremely high QS values of Fe 2+ in the A site (as high as~4.4 mm/s) and the partial decrease of the Fe Kβ satellite peak, which have been interpreted as evidence for an electronic spin transition or transitions in bridgmanite in the lower mantle [e.g., Badro et al, 2004;Li et al, 2004Li et al, , 2006 , 2008;Grocholski et al, 2009;McCammon et al, 2008McCammon et al, , 2010Catalli et al, 2010Catalli et al, , 2011Hsu et al, 2010Hsu et al, , 2011Fujino et al, 2012Fujino et al, , 2014. However, it has been shown in recent firstprinciple calculations that the extremely high QS is a result of the pressure-induced local lattice distortion [Bengtson et al, 2008[Bengtson et al, , 2009Hsu et al, 2010Hsu et al, , 2011Hsu et al, , 2012Hsu and Wentzcovitch, 2014]. However, it has been shown in recent firstprinciple calculations that the extremely high QS is a result of the pressure-induced local lattice distortion [Bengtson et al, 2008[Bengtson et al, , 2009Hsu et al, 2010Hsu et al, , 2011Hsu et al, , 2012Hsu and Wentzcovitch, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown in recent firstprinciple calculations that the extremely high QS is a result of the pressure-induced local lattice distortion [Bengtson et al, 2008[Bengtson et al, , 2009Hsu et al, 2010Hsu et al, , 2011Hsu et al, , 2012Hsu and Wentzcovitch, 2014]. It has also been argued that Fe 3+ in the A site with much lower QS should also remain in the high-spin state especially in Al-bearing bridgmanite, in which Fe 3+ is expected to be predominantly in the A site [e.g., Vanpeteghem et al, 2006;Hsu and Wentzcovitch, 2014]. Based on these results, Fe 2+ in the distorted A site preserves its high-spin electronic configuration in the lower mantle, instead of assuming the intermediate-spin state or the low-spin configuration suggested in some experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, both Fe 3+ and Fe 2+ in the A site have been reported to remain in the HS state throughout the entire lower-mantle pressure range (24-130 GPa) (Dorfman et al, 2015;Hsu et al, 2010Hsu et al, , 2011Lin et al, 2016). The extremely high quadrupole splitting has alternatively been interpreted as the occurrence of the intermediate-spin state in bridgmanite (Hsu & Wentzcovitch, 2014;Lin et al, 2008;McCammon et al, 2008). The extremely high quadrupole splitting has alternatively been interpreted as the occurrence of the intermediate-spin state in bridgmanite (Hsu & Wentzcovitch, 2014;Lin et al, 2008;McCammon et al, 2008).…”
Section: Resultsmentioning
confidence: 99%